Gender and innovation processes in rice-based systems - Luis, Joyce S.; Villanuva, D.; Puskur, Ranjitha (International Rice Research Institute, 2018)
This GRiSP report is based on the perspectives of women and men from three rice-growing villages in the Nueva Ecija province of the Philippines.